Application of SWAT Hydrological Model to Simulate Flow of Seti-Gandaki Basin - KC, Manisha; Dhakal, Naba Raj; Aryal, Insaf; Marahatta, Suresh (Jalawaayu, 2023)
The Soil and Water Assessment Tool (SWAT), a semi-distributed hydrological model, has been used for the Seti-Gandaki River Basin (SGRB) to simulate streamflow. Further, SWAT was assessed to study water balance of the basin. This study primarily focuses on different features of hydrological modeling like multi-site calibration and validation of the streamflow with a view to check the reliability of the model in the high precipitation basin of Nepal. The statistics performance of the model is evaluated using various statistical test like Nash-Sutcliffe, RMSE, and Kling Gupta Efficiency (KGE). Moreover, the study used various statistical parameters like Nash-Sutcliffe efficiency (NSE), Percentage Bias (PBIAS), Coefficient of Variation (R2), ratio of the root mean square error to the standard deviation of measures data (RSR), and Kling Gupta Efficiency (KGE) to evaluate the performance of the model and carryout 0.93(0.89), -0.04(-21.87), 0.95(0.94), 0.26(0.34), and 0.85(0.76), respectively, for calibration (and validation) at Damauli station. The mean annual flow and annual precipitation at SGRB was observed to be 209 m3/s and 2866 mm, respectively. About 20% of annual precipitation seems to be lost as evapotranspiration. The statistics results showed that the model performed better for daily and monthly periods. Overall, the versatility and reliability of SWAT is an appropriate hydrological modeling tool for water resources over the study region. The output of the study can be helpful for the planning and management of water resources in high precipitation basins.